Efficacy of Core Muscle Stabilization in Chronic Nonspecific Low Back Pain Patients – A Systematic Review - Mohammed Luqman, Sulaiman; K., Kotteeswaran; Saravan, Kumar (INTI International University, 2023)
Background: Low back pain referred as pain localized between the 12th rib and the inferior gluteal folds with included leg pain sometimes not, most cases are nonspecific but in about 10% of cases a specific cause is identified. The major causes of low back pain are weakness of superficial trunk muscles, abdominal muscles and motor control or delayed activation of deep muscles (multifidus and transversus abdominis). Hence Core Stabilization exercise provides greater support to the spine, control of lumbar deep muscles and pelvis, and integration of activity of superficial and deep trunk muscles. Aim:The aim of the study is to determine the efficacy of core muscle stabilization exercise in chronic nonspecific low back pain patients. Search Method: Studies were collected from databases Google scholar, PubMed, Cochrane library, Research gate, CINAHL Medicine. Methodology: Inclusion criteria was Randomized or quasi-randomized controlled trial studies and Experimental study design. Sample size was 245 articles, 188 articles were collected from Google scholar, 28 articles from PubMed, and 29 articles from Cochrane library. Methodology of the Study was designed as Systematic review. Results: Out of 245 published studies, we selected 14 articles which describing about efficacy of core muscle stabilization exercise in chronic nonspecific low back pain, among which 8 articles discussed about the effectiveness of core stabilization exercise, 2 articles about lumbar stabilization, 2 articles about Pilates based exercise, 2 articles about segmental stabilization in reducing chronic nonspecific low back pain. Conclusion: By reviewing the study, we conclude that core muscle stabilization exercise is effective in reducing the chronic nonspecific low back pain (CNSLBP).